2019
DOI: 10.3390/w11122511
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Water Filling and Air Expelling Process in a Pipe with Multiple Air Valves under Water Slow Filling Condition

Abstract: This paper investigates the physical processes involved in the water filling and air expelling process of a pipe with multiple air valves under water slow filling condition, and develops a fully coupledwater–air two-phase stratified numerical model for simulating the process. In this model, the Saint-Venant equations and the Vertical Average Navier–Stokes equations (VANS) are respectively applied to describe the water and air in pipe, and the air valve model is introduced into the VANS equations of air as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The results showed that the rapid compression of an enclosed air pocket caused its temperature to rise, accompanied by the white mist phenomenon of water vapor. Liu et al [17] experimentally and numerically studied the low velocity water-filling process in a simple pipeline system with multiple air valves and incorporated the air valve model into the gas phase equation as a source term to study water-air two-phase stratified flow, and the experimental air velocity and pressure are in agreement with the numerical results. Huang et al [18] utilized PIV to investigate the water flow velocity near the entrapped air pockets at the local high-point of pressurized pipelines.…”
Section: Introductionmentioning
confidence: 78%
“…The results showed that the rapid compression of an enclosed air pocket caused its temperature to rise, accompanied by the white mist phenomenon of water vapor. Liu et al [17] experimentally and numerically studied the low velocity water-filling process in a simple pipeline system with multiple air valves and incorporated the air valve model into the gas phase equation as a source term to study water-air two-phase stratified flow, and the experimental air velocity and pressure are in agreement with the numerical results. Huang et al [18] utilized PIV to investigate the water flow velocity near the entrapped air pockets at the local high-point of pressurized pipelines.…”
Section: Introductionmentioning
confidence: 78%
“…The pressure in the pipeline fluctuates greatly, resulting in a complex and changeable water-gas two-phase flow pattern. This directly affects the safe operation of the water supply system [4]. Many water supply projects to be built have the characteristics of long pipelines, large flows, and great elevation fluctuations [5].…”
Section: Introductionmentioning
confidence: 99%